(untitled) - Blood, Douglas C. (London, 1999)
This superb 2nd Edition of the indispensable veterinary dictionary includes 13,000 new entries bringingit right up to date with veterinary medicine today.
Keywords: Veterinary Medicine,Veterinary medicine,Thuốc thú y,Thuốc thú y; English,Nước Anh